Total sleep deprivation reduces top-down regulation of emotion without altering bottom-up affective processing. - Anthony R Stenson (Public Library of Science (PLoS), 2021)
Sleep loss is reported to influence affective processing, causing changes in overall mood and altering emotion regulation. These aspects of affective processing are seldom investigated together, making it difficult to determine whether total sleep deprivation has a global effect on how affective stimuli and emotions are processed, or whether specific components of affective processing are affected selectively. Sixty healthy adults were recruited for an in-laboratory study and, after a monitored night of sleep and laboratory acclimation, randomly assigned to either a total sleep deprivation condition (n = 40) or a rested control condition (n = 20). Measurements of mood, vigilant attention to affective stimuli, affective working memory, affective categorization, and emotion regulation were taken for both groups. With one exception, measures of interest were administered twice: once at baseline and again 24 hours later, after the sleep deprived group had spent a night awake (working memory was assessed only after total sleep deprivation). Sleep deprived individuals experienced an overall reduction in positive affect with no significant change in negative affect. Despite the substantial decline in positive affect, there was no evidence that processing affectively valenced information was biased under total sleep deprivation. Sleep deprived subjects did not rate affective stimuli differently from rested subjects, nor did they show sleep deprivation-specific effects of affect type on vigilant attention, working memory, and categorization tasks. However, sleep deprived subjects showed less effective regulation of negative emotion. Overall, we found no evidence that total sleep deprivation biased the processing of affective stimuli in general. By contrast, total sleep deprivation appeared to reduce controlled processing required for emotion regulation.